TANGGUNG JAWAB PENGELOLA OBJEK WISATA TERHADAP PENGUNJUNG DI TAMAN WISATA ALAM MAYANG KOTA PEKANBARU - Wildaniati Wildaniati; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In Pekanbaru City, there is the Alam Mayang Tourism Park, which is one of the tourist parks that people like to visit, both the people of Pekanbaru City and the migrant communities from various regions, so the tourism park must prioritize the safety and security of visitors. Article 20 of Law Number 10 of 2009 concerning Tourism Every tourist has the right to obtain accurate information about tourist attractions, tourism services in accordance with standards, legal and security protection, health services, personal rights protection and insurance protection for high-risk tourism activities. Therefore, the purpose of writing this essay, namely: first, To find out the responsibility of the tourist management of visitors to the Mayang Nature Tourism Park Pekanbaru City based on Law Number 10 of 2009 concerning Tourism. Second, to find out the constraints of the safety and security of visitors at the Mayang Nature Tourism Park, Pekanbaru City. This type of research can be classified in the type of empirical or sociological legal research, because in this study the author immediately conducts research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Mayang Nature Tourism Park in Pekanbaru City. Data sources used, namely: primary data, secondary data and tertiary data. Data collection techniques in this study with Interviews, Questionnaires and Literature Studies. Conclusions can be obtained from the results of the first study, as referring to several cases that occurred such as Visitors experiencing cruelty, being injured while traveling and being injured while using flying fox, in this case the manager is not responsible for the losses suffered by the Visitors, all should losses borne by the company Mayang Nature Tourism Park Pekanbaru City. Second, the factors that influence the lack of the realization of legal responsibility from the manager of the Pekanbaru City Nature Park for accidents or losses experienced by pengunung, namely lack of public awareness, inadequate facilities / facilities and weak supervision from the Government. The author's advice is to the regional government for the future in order to increase its supervision of the tourism park, whether it is the major natural tourism park in the city of Pekanbaru or other tourist parks. To the company Mayang Nature Tourism Park Pekanbaru City in order to improve its services, is responsible for the losses experienced by Visitors, provide adequate facilities, so that legal protection for visitors can be obtained and can be realized properly.Keywords: Legal Protection - Visitors of Alam Mayang Tourism Park